Coronavirus disease 2019 (covid-19): mechanisms, differential diagnosis and influence of intervention measures (Research, Society and Development, 2020)
Coronaviruses are viruses with simple RNA, whose family can be subdivided into alpha, beta, gamma and delta-coronavirus, which result in infectivity in animals and humans. SARS-CoV-2 has several mechanisms that contribute to its entry and pathogenicity in humans, using the S glycoprotein, which binds to ECA II in the host cell and uses it as an apparatus for replication, as an aid. This paper aims to describe characteristics and comparability between coronaviruses, reports on their virulence factor, clinical data presented by the infected, as well as the main forms of diagnosis, emphasis on molecular tests and the collaboration of imaging for a better prognosis, in addition to citing important intervention measures and describe the importance of these interventions under the large number of cases. This study is a literature review, in which articles indexed in the databases were selected: Pubmed, Scielo and Lilacs, using the terms as descriptors: Coronavirus infections; Covid-19; Virology; Diagnostic Imaging. Where, after content analysis proposed by Bardin (2008) and Minayo (2001) and selection, a total of 37 articles were elected, between the years 2019 and 2020. In conclusion, studies have shown the effectiveness of including intervention measures in combating the new Coronavirus, as well as in other respiratory transmission pathologies. RT-PCR is a very sensitive laboratory technique, which is used for viral detection. The use of imaging tests has contributed to greater reliability in the results.